Preparation and characterizations of latex/filler nanocomposites - Omar, Mohamad Firdaus; Mohamad, Nuriah; Ali, Fathilah (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
Latex compounding which incorporates various types of clays as filler to the rubber can significantly give reinforcement in the rubber matrix when rubber/clay nanocomposites are formed, but the filler agglomerates. Thus, study was conducted by using Kaolin clay as the filler in the rubber nanocomposites with silane coupling agent to functionalize the surface of the filler. This study was done in order to investigate the mechanical properties of various functionalized Kaolin in latex nanocomposites, to prepare various ratios of Kaolin to rubber, and to characterize mechanical, thermal and morphological properties of the Kaolin in latex nanocomposites. To achieve these, six types of silane coupling agents was used for Kaolin filler surface functionalization purpose during the filler’s incorporation in latex compounding. The optimized coupling agent, USi-7301 (?-chloropropyltrimetoxysilane) – with tensile strength value of 32.77 MPa, elongation at break value of 632.589 % and force at break value of 6.737 N – was used to further functionalize Kaolin filler in different ratios so as to achieve the optimum mechanical, thermal and morphological properties of the filler in the polymer matrix. Universal tensile machine was used to analyze the mechanical properties of the nanocomposites, while the Scanning Electron Microscopy (SEM) and Differential Scanning Calorimetry (DSC) were used to observe the morphological and thermal properties of the nanocomposites, respectively. The results showed that reducing the Total Solids Content (TSC) of Kaolin filler to 26 % somehow showed the optimized properties of the nanocomposites, giving 34.00 MPa tensile strength, 576.494 % elongation at break and 6.564 N force at break. Rough surface morphology was observed under SEM suggesting the occurrence of phase separation between the hydrophilic filler and the hydrophobic rubber matrix. In the DSC plot, sample with USi-7301 and with functionalized Kaolin filler 26 % TSC showed glass transition temperature shifted to lower region compared to normal nitrile rubber. The reinforcement of nanocomposites formed will not only enhance the properties of the nanocomposites, but is also economically feasible thus brings advantages to the industry. ********************************************************************* Penyebatian lateks yang menggabungkan pelbagai jenis tanah liat sebagai pengisi dalam getah dapat memberi pengukuhan dalam matriks getah dengan ketara apabila nanokomposit getah / tanah liat terbentuk, tetapi pengisi mengagregat. Oleh itu, kajian dijalankan dengan menggunakan tanah liat Kaolin sebagai pengisi dalam nanokomposit getah dengan ejen gandingan silan untuk menambah-fungsi permukaan pengisi tersebut. Kajian ini dilakukan untuk mengenalpasti sifat mekanik pelbagai Kaolin (yang berfungsi) dalam nanokomposit lateks, untuk menyediakan pelbagai nisbah Kaolin terhadap getah, dan untuk mencirikan sifat mekanik, haba dan morfologi Kaolin dalam nanokomposit lateks. Untuk mencapainya, enam jenis ejen gandingan silan digunakan untuk tujuan menambah-fungsi permukaan pengisi Kaolin semasa penggabungan pengisi dalam penyebatian lateks. Ejen gandingan silan yang paling optimum, USi-7301 (?-silan kloropropiltrimetoksi) - dengan nilai kekuatan tegangan 32.77 MPa, nilai pemanjangan ketika pemutusan 632.589% dan kekuatan daya ketika pemutusan 6.737 N - digunakan dengan lebih lanjut untuk menambah-fungsi pengisi Kaolin dalam nisbah yang berbeza untuk lebih mencapai sifat mekanikal, haba dan morfologi optimum pengisi dalam matriks polimer lateks. Mesin tegangan universal digunakan untuk menganalisis sifat mekanik nanokomposit, sementara Mikroskopi Elektron Pengimbasan (SEM) dan Kalorimetri Pengimbasan Berbeza (DSC) digunakan untuk menganalisa sifat morfologi dan haba nanokomposit tersebut. Hasil kajian menunjukkan bahawa pengurangan Jumlah Kandungan Pepejal (TSC) pengisi Kaolin kepada 26% menunjukkan sifat optimum nanokomposit, dengan kekuatan tegangan 34.00 MPa, pemanjangan ketika pemutusan sebanyak 576.494% dan daya ketika pemutusan sebanyak 6.564 N. Morfologi permukaan kasar diperhatikan di bawah SEM dan ia menunjukkan berlakunya pemisahan fasa antara pengisi hidrofilik dan matriks getah hidrofobik. Dalam plot DSC, sampel dengan USi-7301 dan dengan pengisi Kaolin yang difungsikan dengan 26% TSC menunjukkan suhu peralihan kaca beralih ke kawasan yang lebih rendah berbanding getah nitril biasa. Pengukuhan nanokomposit yang terbentuk bukan sahaja akan meningkatkan sifat nanokomposit, tetapi juga dapat dilaksanakan secara ekonomi sehingga memberi banyak kelebihan kepada industri.